Efficacy determination of paint-brush flower (Klenia longiflora) o suppression of meloidogyne javanica and growth of tomato plants - Moremi, Makgoka Given (My University, 2019)
Plant extracts exhibited broad spectrum of activities against root-knot (Meloidogyne species) nematodes and had long been considered as an attractive alternative due to their being biodegradable and posing limited risk hazards to the environment, animal and human health. Additionally, the materials had been dubbed as being of low-input costs and had been viewed as being easy to apply in agricultural systems. The objective of the current study was to investigate the efficacy of paint-brush flower (Kleinia longiflora) either as fermented or granular formulations on suppression of M. javanica and their related effects on growth of tomato (Solanum lycopersicum) plants under field and greenhouse conditions. Fermented crude extracts were applied at 0, 2, 4, 8, 16, 32 and 64%, whereas granular materials were applied at 0, 2, 4, 6, 8, 10 and 12 g. Regardless of the product, the treatments were arranged in randomised complete block design (RCBD), with 12 replications. Kleinia longiflora plants were collected from the wild, chopped into pieces, oven-dried at 52⁰C and fermented in effective microorganisms (EM) for 14 days, whereas the remained were retained for use as granular formulation. Tomato seedlings cv. ꞌFloradadeꞌ were used as test plants inoculated with 2500 eggs and second-stage juveniles (J2) of M. javanica. At 56 days after the treatments, nematode and plant variables were collected, prepared using appropriate methodologies and subjected to analysis of variance using Statistix 10.0 software to generate means. Plant variables were subjected to the Curve-fitting Allelochemical Response Data (CARD) computer-based model to generate appropriate biological indices. Nematode and mineral elements variable means were subjected to lines of the best fit. Findings showed second-stage juveniles (J2) in roots, J2 in soil, eggs and Pf under increasing concentration were highly significant and exhibited negative quadratic relationship. The model explained the associations by 82, xvii 81, 74 and 76%, respectively. In granular formulation, the product had no significant effects on nematode population densities. The fermented crude extracts significantly affected and exhibited positive quadratic relations for dry fruit mass, chlorophyll content, dry shoot mass, number of flowers, plant height, number of fruit and stem diameter of tomato plants. The model explained the relationship by 97, 94, 95, 96, 94, 97 and 96%, respectively. In contrast, in granular formulation, the product had significant effects and positive exhibited quadratic relations on Chlorophyll content under field and greenhouse, plant height, dry root mass and dry shoot mass. The model explained the relationships by 52, 45, 56, 47 and 59%, respectively. Plant variables and increasing concentration of the products exhibited density-dependent growth patterns for both formulations, with overall sensitivity (∑k) values of 1 and 11, respectively. In fermented liquid and granular formulations, the Mean Concentration Stimulation Point (MCSP) values were derived at 1.97% and 2.84 g, respectively. The increasing concentration of fermented K. longiflora also had significant effects and exhibited negative quadratic relations on the accumulation of K, Na and Zn in leaf tissues of tomato plants. The model explained the associations with 87, 94 and 94%, respectively. In conclusion, the findings in the current study suggested that the nematicidal chemicals in K. longiflora could not be released through irrigation water but could be released into solution through microbial degradation. Also, at low concentration suitable for use without inducing phytotoxicity, the products in either formulation could improve the accumulation of certain nutrients in leaf tissues of tomato plants.
Thesis (M. Agric. (Plant Protection)) -- University of Limpopo, 2019
Keywords: Paint-brush flower; Meloidogyne Javanica; Tomato plants; Root-knot; Root-knot nematodes; Tomato root-knot nematode